Pendampingan Program Latihan dan Pengaturan Gizi Atlet Klub Bolavoli Aksi Muda Kabupaten Magetan - Ningsih, Yuni Fitriyah; Utomo, Andri Wahyu; Arafat, Himawan Fajar (Journal of Sport Moovera (JSM), 2023)
This community service activity is in partnership with the Magetan Regency Youth Action volleyball club which is located at the home base of the Youth Action volleyball field in Sobontoro Village, Karas District, Magetan Regency, which is 23.0 km from Madiun PGRI University. The youth action volleyball club has never been provided with assistance with a volleyball training program and regulation of the athlete's nutritional role, this is due to a lack of superior human resources in coaching volleyball clubs which have many participants in training. Therefore, the service program that is carried out aims to increase understanding, knowledge related to training programs, knowledge of athletes' nutrition arrangements both daily, training or competition. The method applied is using the pretest and posttest, the model before being given the material, practice and after being given the material, practice with advanced techniques evaluating the results of the participants' understanding of the service to find out the level of understanding and knowledge about training programs and athletes' nutrition arrangements. The results in the implementation of mentoring seem to have increased from the initial pretest and posttest participants of 62, namely all members including administrators, coaches and volleyball athletes experienced an increase in knowledge, understanding of the pretest and posttest with an average score of 31.50 while the number of negative rank (difference ) is 0. This value indicates that there is no decrease (reduction) from the pretest and posttest scores. Then the ties value shows a value of 0 which can be interpreted that there are no subjects who have the same value from the pretest and posttest scores